2021
DOI: 10.1002/cbdv.202100734
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of 2‐Methylisoborneol in Forest Soil**

Abstract: Microorganisms use a complex array of chemical compounds to interact with their surroundings. They produce and process different molecules in response to changes in the environment or in their metabolism. One of the most well‐known volatile organic compounds produced by microorganisms is the C11‐terpenoid 2‐methylisoborneol (2‐MIB), which has received attention because of the off‐flavor it confers to fresh and reservoir water as well as to cultured fish. Cleaning water supplies of the off‐flavor 2‐MIB has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…16 Drummond et al reported the in-place biodegradation of both naturally generated and spiked synthetic 2-MIB in soil samples. 17 Shao and Du reported that not only the bacteria themselves but also the enzymes separated from 2-MIB degraders also reduced the 2-MIB concentration and linked the mechanism with NADdependent dehydratase. 18 Other strains of bacteria were also demonstrated to degrade 2-MIB efficiently, including Micrococcus sp., Pseudomonas sp., Flavobacterium sp., Acidobacteriacea, Brevibacterium, and Bacillus fusiformis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Drummond et al reported the in-place biodegradation of both naturally generated and spiked synthetic 2-MIB in soil samples. 17 Shao and Du reported that not only the bacteria themselves but also the enzymes separated from 2-MIB degraders also reduced the 2-MIB concentration and linked the mechanism with NADdependent dehydratase. 18 Other strains of bacteria were also demonstrated to degrade 2-MIB efficiently, including Micrococcus sp., Pseudomonas sp., Flavobacterium sp., Acidobacteriacea, Brevibacterium, and Bacillus fusiformis.…”
Section: Introductionmentioning
confidence: 99%
“…2-MIB degraders were also successfully isolated from the sludge of a fish culture system and demonstrated to effectively reduce 2-MIB from ∼500 to <100 ng/L over 3 days . Drummond et al reported the in-place biodegradation of both naturally generated and spiked synthetic 2-MIB in soil samples . Shao and Du reported that not only the bacteria themselves but also the enzymes separated from 2-MIB degraders also reduced the 2-MIB concentration and linked the mechanism with NAD-dependent dehydratase .…”
Section: Introductionmentioning
confidence: 99%
“…The methylated monoterpene 2-methylisoborneol 1 has been described, for example, in Streptomyces and Actinomyces species with an unpleasant muddy flavor and an extremely low odor threshold of 0.042 µg L −1 in water [4]. Furthermore, 2-methyl-2-bornene 2, 1-methylcamphene 3, and 2-methylenebornane 4 have been described in forest soil [5], and the methylated monoterpenes and monoterpenoids 2-methylgeraniol 5, 2-methyllinalool 6, 2-methyllimonene 7, and 2-methyl-α-terpineol 8, have been identified as products of Nannocystis exedens [6] (Figure 1). Harms et al investigated methylated sesquiterpenes such as iso-β-elemene and isogermacrene, which were synthesized with a sesquiterpene synthase and showed potential as flavor compounds.…”
Section: Introductionmentioning
confidence: 99%